Use of Communication Technology to Improve Clinical Trial Participation in Adolescents and Young Adults With Cancer: Consensus Statement From the Children's Oncology Group Adolescent and Young Adult Responsible Investigator Network. Issue 3 (March 2022) - Avutu, Viswatej; Monga, Varun; Mittal, Nupur; Saha, Aniket; Andolina, Jeffrey R.; Bell, Danielle E.; Fair, Douglas B.; Flerlage, Jamie E.; Frediani, Jamie N.; Heath, Jessica L.; Kahn, Justine M.; Reichek, Jennifer L.; et al.
Abstract : Adolescents and young adults (AYAs; age 15-39 years) with cancer are under-represented in cancer clinical trials because of patient, provider, and institutional barriers. Health care technology is increasingly available to and highly used among AYAs and has the potential to improve cancer care delivery. The COVID-19 pandemic forced institutions to rapidly adopt novel approaches for enrollment and monitoring of patients on cancer clinical trials, many of which have the potential for improving AYA trial participation overall. This consensus statement from the Children's Oncology Group AYA Oncology Discipline Committee reviews opportunities to use technology to optimize AYA trial enrollment and study conduct, as well as considerations for widespread implementation of these practices. The use of remote patient eligibility screening, electronic informed consent, virtual tumor boards, remote study visits, and remote patient monitoring are recommended to increase AYA access to trials and decrease the burden of participation. Widespread adoption of these strategies will require new policies focusing on reimbursement for telehealth, license portability, facile communication between electronic health record systems and advanced safeguards to maintain patient privacy and security. Studies are needed to determine optimal approaches to further incorporate technology at every stage of the clinical trial process, from enrollment through study completion.